Pengenalan Pembangkit Listrik Skala Pikohidro Model Kanal ditempatkan pada Saluran Irigasi Kapasitas 300 Watt - Muhammad Suyanto; Syafriyudin Syafriyudin; Subandi Subandi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: The potential of alternative energy that is quite realistic can be used as one of the studies in new and renewable energy. such as the flow of irrigation water and solar energy that is always there, in the territory of Indonesia. The purpose of community service, namely the introduction of hybrid pico-hydro, is used for street lights, around the neighborhood. Method: This community service, utilizing irrigation flows to create a small-scale power generation system is named (pico-hydro). To increase the output power capacity, a hybrid system is made, namely picohydro (Ph) and solar panels so that charging the battery is faster so that the power is greater. Limitation: The picohydro generator, equipped with a water canals, aims to raise the water level and focus the flow into the mill. Result: The test results on pico-hydro generate a voltage on a DC generator of 13.2V and a current of 2.3A. While the solar panel generates an output voltage of 13.43V and a current of 2.23A. Contribution: The conclusion is that the higher the rotation of the waterwheel, the voltage and current of the generator will follow up. As well as solar panels the getting hotter, the sun's light increases, the voltage and current increase.